Motivación y el aprendizaje del área de Comunicación en los estudiantes de segundo grado de una Institución Educativa de Lima, 2020 - Rodriguez Mercedes, Ana Sofia (2022)
The purpose of this research is to determine the type of relationship between motivation and learning in the Communication Area in second grade students of an educational institution in Lima, 2020. The type of research is descriptive correlational with a non-experimental design with a population of 28 students. The instrument used was the "Motinex" questionnaire to measure the motivation variable in its two dimensions intrinsic motivation and extrinsic motivation, and to measure learning in the Communication area, the record of notes from that area in its three dimensions was used orally, reads various types of written texts and writes various types of texts. These tools allowed us to collect the necessary information and measure the variables for their corresponding correlation and Spearman's Rho comparison, which had a value P=0.0048 < 0.05, concluding that, if there is a positive relationship between motivation and student learning, Communication area in second grade students.